2017
DOI: 10.3174/ajnr.a5339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Deposition in the Brain in Frontotemporal Dementia and Its Correlation with Behavioral Traits

Abstract: BACKGROUND AND PURPOSE:Brain iron deposition has been implicated as a major culprit in the pathophysiology of neurodegeneration. However, the quantitative assessment of iron in behavioral variant frontotemporal dementia and primary progressive aphasia brains has not been performed, to our knowledge. The aim of our study was to investigate the characteristic iron levels in the frontotemporal dementia subtypes using susceptibility-weighted imaging and report its association with behavioral profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…[22][23][24][25] The technique was traditionally performed in the brain using 3D acquisition, which FIGURE 3: SWI fusion maps of left kidneys in rabbits obtained at baseline (1 ) and week 2 (2 ), week4 (3 ), week 6 (4 ), and week 8 (5 ) following UUO. [22][23][24][25] The technique was traditionally performed in the brain using 3D acquisition, which FIGURE 3: SWI fusion maps of left kidneys in rabbits obtained at baseline (1 ) and week 2 (2 ), week4 (3 ), week 6 (4 ), and week 8 (5 ) following UUO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] The technique was traditionally performed in the brain using 3D acquisition, which FIGURE 3: SWI fusion maps of left kidneys in rabbits obtained at baseline (1 ) and week 2 (2 ), week4 (3 ), week 6 (4 ), and week 8 (5 ) following UUO. [22][23][24][25] The technique was traditionally performed in the brain using 3D acquisition, which FIGURE 3: SWI fusion maps of left kidneys in rabbits obtained at baseline (1 ) and week 2 (2 ), week4 (3 ), week 6 (4 ), and week 8 (5 ) following UUO.…”
Section: Discussionmentioning
confidence: 99%
“…SWI combined the magnitude and phase information to provide high sensitivity to susceptibility differences, such as between superparamagnetic materials including iron and surrounding tissues. [22][23][24][25] The technique was traditionally performed in the brain using 3D acquisition, which FIGURE 3: SWI fusion maps of left kidneys in rabbits obtained at baseline (1 ) and week 2 (2 ), week4 (3 ), week 6 (4 ), and week 8 (5 ) following UUO. The maps show the significant changes of SWI signal intensity in the cortex and medulla, and the thickness of renal parenchyma increases at week 2 compared with baseline, since then the r value gradually decreases over time.…”
Section: Discussionmentioning
confidence: 99%
“…49 Significant iron deposition in the behavioral variant FTD (bv-FTD) has been noted in bilateral superior frontal gyri, bilateral temporal pole, bilateral anterior cingulate gyri, putamen and right hemispheric insula, precentral gyrus, hippocampus, and red nucleus. 12 In patients with primary progressive aphasia (PPA), increased iron deposition has been noted in the left temporal pole. Direct comparison between bv-FTD and PPA has revealed enhanced iron deposition in the right superior frontal gyrus in patients with bv-FTD.…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%
“…Direct comparison between bv-FTD and PPA has revealed enhanced iron deposition in the right superior frontal gyrus in patients with bv-FTD. 12 Vascular Dementia (VaD) Previous positron emission tomography (PET) studies have shown that hypometabolism in deep structures and the frontal region of the brain is a sensitive marker of subcortical vascular dementia. Only limited studies exist on iron accumulation related to the condition.…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%
“…Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple system atrophy (MSA), dementia with Lewy bodies, amyotrophic lateral sclerosis, Huntington’s disease (HD), frontotemporal dementia, corticobasal degeneration, and progressive supranuclear palsy (PSP) are primarily characterized by the deposition of insoluble protein aggregates which colocalize with iron (Coffey et al, 1989; Berg and Hochstrasser, 2006; Muller and Leavitt, 2014; Wang et al, 2016; Fernández et al, 2017; Lee et al, 2017; Sheelakumari et al, 2017; Kaindlstorfer et al, 2018; Lane et al, 2018; Moreau et al, 2018), suggesting a link between those clinically and pathologically distinct disease entities. This raises the question whether iron dyshomeostasis represents a critical factor in initiating neurodegeneration, whether it contributes to acceleration of widespread pathology as a result of nerve cell death and the consecutive release of intracellular components or whether neurodegeneration and iron accumulation constitute two completely unrelated events appearing in parallel.…”
Section: Introductionmentioning
confidence: 99%